DESIGNING AND MAINTAINING GOOD POLICIES FOR THE DEVELOPMENT OF THE SOUTHEAST ASIAN COUNTRIES - Wie, Thee Kian (P2E-LIPI, 2013)
The first part of this paper highlighted that there is wide diversity among all ten Southeast Asian countries. Then the discussion was followed by an assessment of the need to design and maintain good policies for the development of the Southeast Asian countries. In this section, the discussion focused on four main areas such as: (i) sound macroeconomic policies; (ii) the growth and trends in poverty of these countries; (iii) the industrial and technological development of these countries; and (iv) the need to achieve an environmentally sustainable development of these countries, particularly in regard to the preservation of Southeast Asiaâs precious tropical hardwood forests.Â